Blended Learning-based Career Information Needs - Hidayati, Nurul Wahyu; Mulawarman, Mulawarman; Eddy Wibowo, Mungin (Study Program of Guidance and Counseling, Postgraduate Program, Universitas Negeri Semarang, 2021)
Career planning is a process that needs to be prepared to achieve career goals. However, since many students have not been able to determine their goals, they often fail in making career decision and planning. Thus, the current study was done to describe Senior High School students’ needs for a blended learning-based career information service model. It was conducted by having a qualitative survey design with Focused Group Discussion (FGD) method participated by 10 Guidance and Counseling teachers through MGBK or Guidance and Counseling Teacher Forum in Demak Regency and career planning scale distributed to 150 students to obtain the descriptive data. After the analysis, it was found that student’s career planning ability is categorized low and counselors experience some difficulties in sharing career information, particularly in terms of available time and method. In this way, career information content developers are suggested to provide digital content of career information so that students can access it outside school hours.